2022
DOI: 10.9734/jeai/2022/v44i930850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Labour Scarcity on Rice Production and Yieldin Guma Local Government Area of Benue State

Abstract: The study assesses the effects of labour scarcity on rice production and yield in Guma Local Government Area of Benue State. Survey research design was adopted; with a population of 5125 registered smallholder rice farmers, out of which 371 respondents were sampled using the multi-stage sampling strategy. The questionnaire was then used to collect data from the sample. Data collected was analyzed using Statistical Package for Social Sciences (SPPS 20.0) from which simple frequencies and percentages were presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It has been reported that the agricultural sector in Nigeria is dominated by small-scale farmers whose farms vary from between 0.10 and 5.99 hectares in size and they make up about 80.35% of all the 29,800 million farm holdings in the country. These farmers use traditional technologies called hoe-cutlass culture and their capital structure is characterized small tools, and mainly dependent on the usage of family labour [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the agricultural sector in Nigeria is dominated by small-scale farmers whose farms vary from between 0.10 and 5.99 hectares in size and they make up about 80.35% of all the 29,800 million farm holdings in the country. These farmers use traditional technologies called hoe-cutlass culture and their capital structure is characterized small tools, and mainly dependent on the usage of family labour [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Human or manual labour has also been reported as the predominant source of labour available to smallholder farmers in Nigeria. These farmers make up about 85% of domestic agricultural output in Nigeria, thus, human labour accounts for the domestic food supply in Nigeria [6,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations